Changes in target ability of nanoparticles due to protein corona composition and disease state - Wenwen Xu; Mingyu Xu; Yumeng Xiao; Lu Yu; Huiru Xie; Xuehua Jiang; Meiwan Chen; Huile Gao; Ling Wang (Elsevier, 2022)
Many studies have shown the influence of protein corona (PC) on the active targeting capability of ligand-modified nanoparticles; however, the influence of clinical status on PC composition and targeting capacity is rarely discussed. In this study, when transferrin-modified PEGylated polystyrene nanoparticles (Tf-PNs) is intravenously injected into mice with non-small cell lung cancer (NSCLC) comorbid with type 2 diabetes mellitus (T2DM), more Tf-PNs accumulated in the tumor tissue than in those of NSCLC model mice. This indicated that PC derived from different states of disease changed the active targeting ability of Tf-PNs. To explain the occurrence of this phenomenon, our analysis of PC from different disease states revealed that Tf (transferrin) modification had no significant effect on the formation of PC, and that the PC from the NSCLC comorbid with T2DM model contained more proteins like fibrin and clusterin. This work demonstrates the impacts of comorbidity, such as with T2DM, on the active targeting capability of ligand-modified nanoparticles, and the results promote the application of nanoparticles for precision medicine.